Hubungan Perilaku Gizi Seimbang, Aktifitas Fisik, Dan Perilaku Sedentari Dengan Status Gizi Pada Remaja - Ashar, Amalia Maysarah; Rezky Aulia Yusuf; Nurul Hikmah B (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
World Health Organization (WHO) defines overweight and obesity as an increase in the accumulation of body fat above standard limits, thereby increasing the risk of other health problems in the body. In light of this, a study was conducted to determine the relationship between balanced nutritional behavior, physical activity, and sedentary behavior in adolescents at SMPN 6 Makassar. This research, a quantitative study with a cross-sectional approach, has practical implications for health professionals and policymakers. The population in this study was all students of SMPN 6 Makassar, totaling 1012 students, with a sample size of 286 respondents. The data analysis, carried out univariately and bivariately using the chi-square test with a significance level of ρ <0.05, revealed some significant relationships. The results of the bivariate analysis study stated that there is a relationship between measuring body weight and nutritional status, where the value (ρ = 0.005), There is a relationship between consuming fruits and nutritional status, where the value (ρ = 0.025), There is a significant relationship between consuming vegetables and nutritional status, where the value (ρ = 0.054), There is a relationship between consuming soda / canned / packaged drinks on nutritional status, where the value (ρ = 0.006 <0.05), There is a relationship between consuming fast food and nutritional status, where the value (ρ = 0.001), There is a relationship between doing physical activity 60 minutes a day with nutritional status, where the value (ρ = 0.043 <0.05) There is a relationship between performing prayers and nutritional status, where the value (ρ = 0.000 <0.05). The conclusion of this study is that there is a relationship between two variables, namely balanced nutritional behavior and physical activity. And there is no relationship in the sedentary behavior variable, a finding that has direct implications for health interventions and policies.